Effects of different epoxidation methods of soybean oil on the characteristics of acrylated epoxidized soybean oil-co-poly(methyl methacrylate) copolymer - V. Tanrattanakul; P. Saithai; E. Dubreucq; J. Lecomte (eXPRESS Polymer Letters)
The effect of the type of epoxidation processes of soybean oil on the characteristics of epoxidized soybean oils (ESOs), acrylated epoxidized soybean oils (AESOs), and acrylated epoxidized soybean oil – poly(methyl metacrylate) copolymers (AESO-co-PMMA) has been investigated. Two epoxidation processes were used: an in situ chemical epoxidation using hydrogen peroxide and formic acid, and a chemo-enzymatic epoxidation using 2 enzymes: Novozyme® 435 (CALB) and a homemade lipase/acyltransferase (CpLIP2). ESOs containing different numbers of epoxide groups/molecule were synthesized. A commercial ESO (Vikoflex® 7170) was employed and it had the highest number of epoxide groups. Acrylation of ESOs was carried out using acrylic acid, and copolymerized with a methyl methacrylate monomer. The chemo-enzymatic epoxidation produced high acid value, particularly from the CpLIP2 (~46–48%) and indicated the formation of epoxidized free fatty acids. In contrast, the ESO synthesized from the chemical epoxidation showed a very low acid value, < 0.6%. The AESOs synthesized from the CALB-based ESO and the chemical-based ESO showed a similar number of acrylate groups/molecule while that from the CpLIP2-based ESO showed a very low number of acrylate groups because the carboxylic groups from the epoxidized free fatty acids impeded the acrylation reaction. The lower the number of acrylate groups the lower was the crosslink density, the Tg, and the gel content in the AESO-co-PMMA copolymer.